Movimentos partidos: geopolíticas da revolução brasileira (1964-1985) - Braga, Sandra Rodrigues (2008)
The bureaucratic-military regimen of 1964 allowed geopolitics a new way of rationalization and technicality of the territory, discourse and power action as well to occupy a central position in the political arena. The territory optimization, aiming at the enlarged reproduction of the capital was carried out thanks to an authoritarian planning that produced a new socioterritorial segmentation of the work. The returning of the military to the headquarters, after twenty-one years commanding the Brazilian State, however, did not represent a backward movement of this geopolitical project. On the contrary, what this thesis intends to demonstrate is that the plan of political opening carried out by General-President Ernesto Geisel, in 1974, had as its main objective to maintain the Great Project, and for that he used the workers politics as one of his tools. The workers issue had become delicate because of the contribution of the workers (by means of salary difficulties) in the conformation of the Brazilian miracle . This way, the first section of this work The long miracle, its saints and epiphanies analyses the regimen economic policies. Such policies were marked both by the fight against inflation and the developmental ideology, that replaced the geopolitical imaginary of Brazil Great (Potency): in the counterpart of the paradise of the medium social class, the salary contention of the industrial army of reserve, up to the limit of hunger. In this context, the revolution of the general state began to face opposition of other images of revolution, as it is showed in the second section of the thesis Goodbye Weapons . This section is a theoretical discussion on parties, syndicates and the workers movement. It follows with the analysis of the situation of the workers social class in Brazil, its different organizations, social projects and ways of facing the regimen. The establishment fighting against these organizations occurred, essentially, in the geopolitics field, that is, by means of mechanisms of control of the material and symbolic territories. In order to get things properly done the regimen used instruments both of physical repression (the information community) and symbolic repression (hiding the resistance ), and, opposing to the Maoist conception of the city surrounding the field, caused the surrounding of the city by the field. The essential objectives of this urban boom were geopolitical: the integration of the national archipelago territory, avoiding offering it to exotic States and ideologies. The cities promoted a new modus vivendi and demands as well, exponentially amplified, with an access to a higher standard of consume. Once the self-criticism of the armed fight was centralized on the smallburgess character of its leadership, the emerging of Lula, a worker in the front of a powerful strike wave of the interregnum 1978-1980, was taken as a booster of a new platform of the workers organization, what, later, would become PT and CUT. In the third section In search of a lost democracy the theoretical debate is retaken on the democratic transitions and specificities of the Brazilian transition. Finally, the workers politics of Geisel is revisited, as well as its reaction to the strikes of the period. Lula would only proclaim the maximization of the work productivity under the capitalism, that is, the exercise of liberty with responsibility , defended by Geisel. We conclude that Lula and his party were revealed as powerful antidotes against the incurable disease of the Communism, first target of the Brazilian military geo-politicians.